A systematic assessment of threats affecting the rare plants of the United States. (November 2016) - Hernández-Yáñez, Haydée; Kos, Justin T.; Bast, Matthew D.; Griggs, Janeisha L.; Hage, Paul A.; Killian, Alex; Loza, M. Isabel; Whitmore, Matthew B.; Smith, Adam B.
Abstract: Characterizing the distribution of threats facing species is a crucial, first step toward designing effective conservation strategy. The last comprehensive analysis of threats facing rare plants in the United States was conducted nearly 20 years ago. Here we systematically analyze the threats facing 2733 rare and vulnerable plants in the US using textual analysis of the most comprehensive database available. In the continental US plants are most commonly threatened by outdoor recreation (affecting 35% of species), especially from off-road vehicles (19%) and hiking and related activities (13%). The next-most common threats are from livestock (33%), residential development (28%), non-native invasives (27%), and roads (21%). In Hawaii invasives threaten 95% of species followed by increases in fire intensity/frequency (26%) then livestock (19%). Multivariate analyses indicate threats do not form distinct "syndromes" (clusters of threats) but rather a single "mega-syndrome" with high degrees of overlap between most threats. We also compared the prevalence of threats to the distribution of research effort. Nearly 75% of threats are understudied relative to their prevalence, including five of the six most common threats while a few rare threats (missing species like pollinators; pathogens; logging; climate-induced ecosystem movement; and crop-based agriculture) receive most of the attention. In comparison to a benchmark assessment from 1998 (Wilcove et al. BioScience 48:607-615) we find little difference in threat prevalence, though temporal trends suggest increasing frequency of nearly all threats. Overall rare plants in the US are affected by a dense network of threats across which research attention is disproportionately directed. Graphical abstract: Highlights: Outdoor recreation is the most common threat to rare plants in the United States. Other common threats include livestock, residential development, and invasives. The network of threats affecting rare plants is highly interconnected. Common threats receive little research attention vis-à-vis their prevalence.